2004
DOI: 10.1016/j.accreview.2004.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Vascular anomalies in Alagille Syndrome: a significant cause of morbidity and mortality

Abstract: Background-Alagille syndrome (AGS) is a dominantly inherited multisystem disorder involving the liver, heart, eyes, face, and skeleton, caused by mutations in Jagged1. Intracranial bleeding is a recognized complication and cause of mortality in AGS. There are multiple case reports of intracranial vessel abnormalities and other vascular anomalies in AGS. The objective of this study was to characterize the nature and spectrum of vascular anomalies in AGS. Methods and Results-Retrospective chart review of 268 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
132
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(139 citation statements)
references
References 14 publications
3
132
0
4
Order By: Relevance
“…In terms of pathophysiology, attention has been given to the possibility that AGS is essentially a defect of vasculogenesis (Kamath et al, 2004). Apart from the frequency of congenital heart disease, it has become clear that other forms of vascular anomaly occur frequently, in up to 9% of AGS patients.…”
Section: Alagille Syndrome (Arteriohepatic Dysplasia) Jagged1 and Nomentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of pathophysiology, attention has been given to the possibility that AGS is essentially a defect of vasculogenesis (Kamath et al, 2004). Apart from the frequency of congenital heart disease, it has become clear that other forms of vascular anomaly occur frequently, in up to 9% of AGS patients.…”
Section: Alagille Syndrome (Arteriohepatic Dysplasia) Jagged1 and Nomentioning
confidence: 99%
“…Apart from the frequency of congenital heart disease, it has become clear that other forms of vascular anomaly occur frequently, in up to 9% of AGS patients. In the review of Kamath et al (2004), there were patients with aneurysms of the basilar arteries, middle cerebral arteries, and aorta, and some had structural anomalies of the internal carotid arteries. From a total of 268 patients reviewed, 25 (9%) had significant noncardiac vascular anomalies and a further 9 subjects had intracranial events in the absence of documented intracranial vascular anomalies.…”
Section: Alagille Syndrome (Arteriohepatic Dysplasia) Jagged1 and Nomentioning
confidence: 99%
“…A more substantial consideration relates to the possibility that ALGS is primarily a vasculopathy. The vascular anomalies of ALGS are widespread, 29 prompting the notion that at least some of the effects are traceable to abnormalities of angiogenesis and the vascular system. There is evidence that the formation of mature tubular bile ducts follows on from development of the intrahepatic arterial network.…”
Section: Pathogenesismentioning
confidence: 99%
“…29 Intracranial bleeding may occur as a consequence of relatively minor head trauma. Studies have identified anomalies of the basilar, carotid, and middle cerebral arteries, 29,30 and renovascular anomalies, middle aortic syndrome, and Moyamoya syndrome have all been reported. The vascular aspects of ALGS are considered further in the next section.…”
Section: Vascular Eventsmentioning
confidence: 99%
“…A number of other genetic syndromes have been reported in association with aortic disease, including but not limited to: Weill-Marchesani syndrome (ADAMTS10 and FBN1) [13]; congenital contractural arachnodactyly (resembles MFS, is characterised by crumpled ears, scoliosis, joint contractures and FBN2 mutations) [14]; Noonan syndrome (mutations in the RAS-MAPK signalling pathway) [15,16]; Alagille syndrome (JAG1) [17] ; X-linked dominant periventricular nodular heteropia, EDS variant (FLNA) [18] and Shprintzen-Goldberg syndrome (SK1) [19].…”
Section: Othermentioning
confidence: 99%